2014
DOI: 10.12988/asb.2014.4843
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of Hyssopus officinalis, Tussilage farfara, Carum copticum extracts against Leishmania major in Iran

Abstract: Leishmania is transmitted by sandflies that ingest the parasite in the amastigote phase resident within macrophages, then inoculate the promastigote phase into body hosts. The present study was conducted to evaluate the in vitro effects of alcoholic extract of Plants on L.major. The extract of aerial parts of plants were obtained by maceration. The in vitro experiments were performed on promastigotes to assess antileishmanial activity of the extracts using glucantime as 194 Fatemeh Tabatabaie et al.a reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Diseases caused by Leishmania are a continuous health problem worldwide due to the emergence of resistance developed by protozoans. Several drugs like meglumine antimoniate, potassium antimonial tartrate, and Amphotericin B are being used as first-line treatments against leishmaniasis, but drug resistance is a major challenge . Therefore, the design of new antileishmanial drugs having less resistance is desperately needed.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diseases caused by Leishmania are a continuous health problem worldwide due to the emergence of resistance developed by protozoans. Several drugs like meglumine antimoniate, potassium antimonial tartrate, and Amphotericin B are being used as first-line treatments against leishmaniasis, but drug resistance is a major challenge . Therefore, the design of new antileishmanial drugs having less resistance is desperately needed.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several drugs like meglumine antimoniate, potassium antimonial tartrate, and Amphotericin B are being used as first-line treatments against leishmaniasis, but drug resistance is a major challenge. 19 Therefore, the design of new antileishmanial drugs having less resistance is desperately needed. In the current work, we explored the consequences of Tl-POMs at an equimolar concentration of thallium against promastigotes of Leishmania tropica and compared it with Amphotericin B.…”
mentioning
confidence: 99%
“…In each test groups (10%), the lesions in 2 animals, out of 10, disappeared completely. The possible mechanism for this effect is through release of nitric acid and tumor necrosis factor from macrophages (10).In another study, peganine exhibited in vitro activity against both extracellular promastigotes as well as intracellular amastigotes residing within murine macrophages in L. donovani then P harmala seeds extract showed significant in vitro and in vivo antileishmanial activities (16). The results of this study mentioned above is in agreement with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a 200-mg amount of ointment was used per mouse per day using cotton applicator. After the end of the treatment period, mice in the experimental and placebo groups were followed for 1 month (10). The Nitrit levels were measured by the Griess reaction, which is an assay for NO production.Peritoneal macrophages were harvested.…”
mentioning
confidence: 99%